Chromatic uniqueness of a family of k4-homeomorphic graphs - Catada-Ghimire S.; Roslan H. (Utilitas Mathematica, 2013)
We shall investigate the chromaticity of K4-homeomorph with exactly two adjacent paths of length two and exactly one path of length one. A sufficient and necessary condition for all the graphs in this family to be chromatically unique shall also be given.